Implementation of Tahsin Al Qur'an Learning with Iqro' Method in Improving Students' Reading of Al Qur'an in SD IT DOD Tanjung Gusta Sunggal District - Nahar, Syamsu; Saputra, Edi; Riyadh, Muhammad (BIRCU, 2021)
This study aims to determine: (1) knowing the planning of learning Tahsin Al Qur'an with the Iqro' method at SD IT DOD Tanjung Gusta, (2) knowing the implementation of learning Tahsin Al Qur'an with the Iqro' method at SD IT DOD Tanjung Gusta, (3) knowing the evaluation of learning Tahsin Al Qur'an with the Iqro method at SD IT DOD Tanjung Gusta. To achieve the above objectives, a qualitative approach is used with a qualitative descriptive type. Data collection is done by using interview, observation and documentation methods. The data are analyzed by reducing the relevant data, presenting the data and drawing conclusions. The results showed that: (1) Planning for Tahsin Al Qur'an learning with the Iqro' method was guided by the learning program that had been designed by the vice principal for student affairs and the coordinator of Thafidz/Tahsin SD IT DOD Tanjung Gusta, the teacher only adjusted the hours of learning and regulate the conditions of students in the classroom, while the necessary preparation itself is the mastery of learning materials and supporting materials such as Arabic writing in order to improve the quality of students' abilities. (2) the implementation of learning Tahsin Al Qur'an with the Iqro method begins with muroja'ah reading the previous Iqro' together, then enters the material. The teacher reads and explains while the students listen to the Iqro' read by the teacher, after that the students read together and write. (3) evaluation of learning Tahsin Al Qur'an with the Iqro' method, daily assessments are carried out at the end of each student learning meeting by being tested one by one in front of the teacher. The assessment of the increase in the level of Tahsin learning stages is by conducting monthly exams, mid-semester exams and end-semester exams.Â